Identification Of Friction Models For Precise Positioning System In Machine Tools - Jamaludin, Zamberi; Chiew, Tsung Heng; Bani Hashim, Ahmad Yusairi; Rafan, Nur Aidawaty; Abdullah, Lokman (Elsevier, 2013)
This paper focuses on friction identification and numerical validation on ball-screw driven XY milling table. Two friction models namely; static friction model and Generalized Maxwell-slip (GMS) model are identified and validated numerically. Static friction model is identified by measuring the control command signals of various constant velocities while friction-position behavior during sliding and pre-sliding regimes is determined to identify GMS model. Parameters of static friction model are estimated using heuristic approa ch while application of piecewise linear functions and theory of superposition in virgin curve are used in approximating the parameters of GMS model. Based on obtained parameters, the models are generated in simulation using MATLAB/Simulink to verify the friction models and glitches formed during motion of low velocity. Simulation results showed that GMS model produced clearer and larger glitches compared to static friction model during low velocity motion. GMS model is capable of characterizing the friction behavior during pre-sliding.